Efektivitas Penerapan Scratch Programming Berkonten Magic Words untuk Meningkatkan Pemahaman Etika Digital Anak Usia Dini 5-6 Tahun - Rizki Ayu Amalia Putri; Amirul Mukminin (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The development of digital technology has increased the intensity of early childhood interactions with digital media. This condition requires the introduction of digital ethics from an early age to prevent the emergence of negative behaviors, such as the use of impolite language, exposure to inappropriate content, and cyberbullying. This study aims to determine the effectiveness of implementing scratch programming with magic words content in improving the understanding of digital ethics in children aged 5-6 years. This study used a quantitative method with a quasi-experimental approach and a one-group pretest-posttest design. The research instrument has passed validity and reliability tests with a Cronbach's Alpha value of 0.70. Data analysis was carried out using the Shapiro-Wilk normality test, the Wilcoxon test, and the N-Gain test. The results of the normality test showed that the pretest and posttest data were not normally distributed, so the analysis was continued using the Wilcoxon test. The Wilcoxon test results showed a significance value <0.001 which indicated a significant difference between the pretest and posttest scores. The results of the N-Gain test obtained an average value of 0.8770 which is included in the high category. Thus, the implementation of scratch programming with magic words content is effective in improving children aged 5-6 years old's understanding of digital ethics.